A Bánság népessége a 18. században - Kókai, Sándor (Közép-Európai Közlemények, 2014)
After signing the Pozsarevac Threaty on 21st August 1718 the area of Bansag got its freedom after the occupation by the Turkish Empire. Despite the region did not fully loose its population during the turkish times, its population decreased significantly and the economy was totally destroyed. The human resources were ensured by organising the Bansag (1718–1778), direct Austrian control and prior to the will of the government in Wien. Our knowledge about the population of the Bansag in the 18th century is poor, especially the times before the 1760s. In terms of the human resources in this region severe differences occurred between the researchers both in the number of the population, in ethnic and lingual structure, in regional distribution, in their origin and identity. Solution for these opposite opinions is possible if we answer the questions correctly by comparative analysis of the known databases following the changes in the 18th century.